Sirup Kulit Kayu Manis Sebagai Produk Ekonomi (Tinjauan Sosial Budaya Pada Masyarakat Meratus Loksado) - Sajidin, Ahmad; Alfisyah, Alfisyah (Universitas Lambung Mangkurat, 2026)
The Meratus indigenous community in the Meratus Mountains. One of their main commodities is cinnamon, which has high economic value and has been processed into products such as cinnamon syrup that is beneficial to health. Despite its great potential, the development of this product is still hampered by socio-cultural constraints. This study aims to identify the efforts made by the community to improve cinnamon bark syrup production among the Meratus people in Loksado District, Hulu Sungai Selatan Regency, as well as to identify the socio-cultural constraints in efforts to improve cinnamon bark syrup production among the Meratus people in Loksado District, Hulu Sungai Selatan Regency. The method used in this study is qualitative research. The data sources used in this study are primary and secondary sources. Data collection was carried out using observation, interviews, and documentation techniques. Based on the results of the study, the following was found: (1) Socio-cultural constraints in increasing the production of cinnamon bark syrup among the Meratus people in Loksado District, Hulu Sungai Selatan Regency. a) Limited social adaptation to innovation. b) The dominance of local traditions and customs on public consumption of products. (2) Community efforts to increase cinnamon bark syrup production among the Meratus people in Loksado District, Hulu Sungai Selatan Regency, namely: a) Human Resources (People) b) Production Equipment (Plant). c) Raw Materials and Product Components (Parts) d) Processing Methods and Technology (Processes) e) Planning and Control Systems (Planning and Controlling).